Stem Cell Aging: Mechanisms, Consequences, Rejuvenation - Geiger, Hartmut; Jasper, Heinrich; Florian, Maria Carolina; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2015)
Aging of somatic stem cells reduces cell function and results in dysfunctional organs and tissues, making it an underlying cause of diseases associated with aging. It might even be the primary cause for age-associated attrition of tissue function in organs that heavily rely on stem cells for maintaining homeostasis, like the skin, blood and intestines. Understanding the molecular and cellular mechanisms involved is critical for developing approaches to attenuate stem cell aging and could pave the way for improved quality of life among the elderly. Written by highly prominent experts in the field, this book presents the current state of knowledge on these mechanisms. It offers insights into stem cell function, explains in detail the mechanisms of stem cell aging in model organisms as well as mammalian systems, and describes related diseases and approaches to attenuating stem cell aging or achieving rejuvenation. The book is intended for all scientists and clinicians working with stem cells, aging mechanisms or age-related diseases.
Introduction -- Stem cells, aging and longevity (overview) -- General mechanisms of stem cell aging (overview) -- Mechanisms of Stem Cell Aging in Model Organisms -- Yeast: Chronological aging -- Divisional aging -- Primarily germline -- stem cell aging -- Drosophila: Male germ line -- Female germ line -- Somatic stem cells (stress and regulation of hematopoietic precursors, intestinal stem cell aging and regulation). Zebrafish -- Mechanisms of Stem Cell Aging in Mammalian Tissues.-Hematopoietic (Mouse/Human) -- Skin (Mouse/Human) -- Intestine (Mouse/Human) -- Muscle (Mouse/Human) -- Neuronal Tissues (Mouse/Human) -- Diseases of Aging and Stem Cells -- Chronic Myeloid Leukemia and Aging of Hematopoietic Stem Cells (Mouse/Human) -- Wound Healing Repair and Aging of Skin Stem Cells (Mouse/Human) -- Stem Cell Rejuvenation Muscle -- Hematopoietic -- Neuronal.
Keywords: Stem cells; Cancer research; Immunology; Hematology; Stem Cells; Cancer Research; Immunology; Hematology